Clustering of non-communicable disease risk factors among adolescents in urban and rural Rajasthan - Virmani, Shiv; Verma, Anjana; Patyal, Ashish; Mathur, Medha; Mathur, Navgeet; Shekhawat, Vasundhara (International Journal Of Community Medicine And Public Health, 2024)
Background: Non communicable diseases (NCDs) are primarily driven by the modifiable risk factors that often emerge during the childhood/adolescence and contribute towards majority of premature deaths during adulthood. This study aimed to assess the prevalence of multiple NCD risk factors and the associated factors among adolescents in urban and rural areas of Rajasthan. Methods: It was a community-based cross-sectional study conducted among 430 school going adolescents. A self-administered questionnaire adapted from STEPS survey format of the WHO and indian adolescent health questionnaire was used; anthropometric measurements were taken using standard procedure. Presence of two or more risk factors in one individual was considered as clustering of NCD risk factors. Results: Prevalence of two risk factors (Dyads) was 48.8% (urban) and 33% (rural), three or more risk factors were found in about 12.1% urban and 7.9% rural adolescents. For “Dyads”, males had OR 3.58 (95% CI 1.9- 6.4) and OR 4.1 (95% CI 2.6-7.9) in urban and rural areas, respectively. The risk of clustering was higher with increasing age [Dyad: OR 1.26 (CI 1.1-5.73) in urban, OR 2.2 (CI 1.56-3.7) in rural; ≥ 3 risk factors: OR 2.3 (CI 1.98-4.11) in urban, OR 1.52 (CI 1.21-4.9)]. Conclusions: Clustering of the risk factors was prevalent among urban as well as rural adolescents emphasizing the importance of developing primary prevention strategies which can be effective across all demographic and socioeconomic backgrounds.